2000
DOI: 10.1161/01.cir.102.25.3039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Influenza Vaccination and Reduced Risk of Recurrent Myocardial Infarction

Abstract: In this study in patients with chronic CHD, vaccination against influenza was negatively associated with the development of new MI during the same influenza season. However, to address causal inference, examination of prospective data sets will be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
4
12

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(181 citation statements)
references
References 36 publications
6
153
4
12
Order By: Relevance
“…However, the ability of the influenza A vaccination to reduce the risk of acute coronary events remains debated, as discordant results have been reported [31][32][33]. The increased platelet activation observed after vaccination in our study might transiently increase the risk of thrombosis in high-risk patients.…”
Section: Inflammation and Platelet Activationsupporting
confidence: 62%
“…However, the ability of the influenza A vaccination to reduce the risk of acute coronary events remains debated, as discordant results have been reported [31][32][33]. The increased platelet activation observed after vaccination in our study might transiently increase the risk of thrombosis in high-risk patients.…”
Section: Inflammation and Platelet Activationsupporting
confidence: 62%
“…influenza vaccination was associated with a reduced risk of recurrent non-fatal MI (OR = 0.33, 95% CI: 0.13-0.82) during the 1997-1998 influenza season 12 and Siscovick and colleagues found that influenza vaccination during the previous year was associated with a reduction in the risk of out-of-hospital cardiac arrest (OR = 0.51, 95% CI: 0.33-0.79). 13 Nichol et al found that receipt of influenza vaccine among a cohort of elderly persons was associated with a reduced risk of hospitalizations associated with a discharge diagnosis code of ischemic heart disease during the 1998-1999 influenza season (OR = 0.80, 95% CI: 0.70-0.91) but not during the 1999-2000 influenza season (OR = 0.90, 95% CI: 0.78-1.03).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Influenza epidemics have been associated with excess mortality attributed to cardiovascular disease, 9,10 although they have not been found to be associated with increased rates of hospitalizations for acute ischemic cardiac events. 11 Recent studies suggest that influenza vaccination may reduce the risk of recurrent MI, 12 primary cardiac arrest, 13 death from cardiovascular disease, 14 and hospitalization for ischemic heart disease. 15 However, results of one study suggest that influenza vaccination is not protective against recurrent coronary events.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, we reported a case-control study in patients with known coronary artery disease; influenza vaccination was associated with a 67% reduction (OR 0.33, 95% CI 0.13 to 0.82, PĎ­0.017) in risk of MI in the subsequent influenza season. 17 In a simultaneous population-based case-control study, Siscovick et al 18 found that after adjusting for demographic, clinical, and behavioral risk factors, influenza vaccination was associated with a 49% reduction (OR 0.51, 95% CI 0.33 to 0.79) in risk of out-of-hospital primary cardiac arrest. Another casecontrol study reported a 50% risk reduction (OR 0.50, 95% CI 0.26 to 0.94, PĎ­0.033) in stroke risk in subjects vaccinated during the year of the study and a 48% (OR 0.42, 95% CI 0.21 to 0.81, PĎ­0.009) risk reduction in those vaccinated during the last 5 years.…”
Section: Infections and Atherosclerosismentioning
confidence: 99%